Power of blank spaces: A critical cartography of China's Belt and Road Initiative. (26th October 2021) - Murton, Galen
Abstract : A variety of maps depict a usefully approximate but inexact network of roads, rails, sea lanes and other infrastructures to represent something called China's Belt and Road Initiative (BRI). And yet, for a global programme that reflects and advances Beijing's new position as a leader of international development, BRI maps remain largely imprecise and unofficial. Taking this as a starting point of critical cartography, I ask why BRI development throughout the Tibet‐Himalaya region remains conspicuously blank on most maps, and what work is accomplished by such cartographic silences. In contrast to this apparent invisibility, however, the BRI is very much present in Nepal – discursively, materially and cartographically. Chinese development programmes are widely anticipated, embraced and promoted as grand and spectacular things throughout Nepal. Following this friction of representation in the case of Chinese development in Nepal, I argue that the apparent paradox between the BRI as invisible thing and BRI as promised future reveals the manifold ways in which infrastructures articulate politics and, vice‐versa, how politics articulate infrastructures.